Corynebacterium urinapleomorphum sp. nov., a new bacterial species isolated from human urine sample - Niang, E.H.A. (New Microbes New Infect, 2019)
Corynebacterium urinapleomorphum sp. nov. stain Marseille-P2799(T) (= CSURP2799; = DSM103272) is a new species from the order Corynebacteriales that was isolated from urine of a 2-month-old child with gastroenteritis.